The influence of constructivism with family and instructor support on students' success and conceptual learning capabilities in science lessons - (:unkn) unknown (My University, 2010)
The purpose of this study is to investigate "the effects of constructivism with family and primary school teachers' support on conceptual learning capabilities and accomplishment of 5. class students attending sound unit in Science Lessons." For this purpose, the influence of education with family support - and/or elementary teacher support - on academic achievement and conceptual learning is investigated. Model of the research can be classified as pre-test - post-test experimental model. © 2010 Elsevier Ltd. All rights reserved.
Keywords: concept; constructivism; Family; success; teacher